Impact of a big political event on stock market: The 2019 Presidential Election case - Christian Vieri Dharmasaputra; Yosia Satya Guna (Jurnal Ekonomi Perusahaan, 2021)
A national-scale political event has a big impact on the country’s economy. The most notorious political event in Indonesia is President and Vice President Election. This study is intrigued by a quest about whether that event impacted the stock market return. More specifically, did the event cause an abnormal stock return? To answer that curiosity, the authors took nine sectors of the Indonesia Stock Exchange as the research object. Each sector consists of 15 companies that are range from the small, medium, and large categories, based on market capitalization, debt/equity, revenue, and return on equity. This approach enables the authors to finally arrive at 135 units of analysis. The data is tested using the paired-samples t-test. This test reveals that there is no difference in abnormal returns before and after the 2019 President’s Election. In other words, there is no effect of the 2019 Presidential Election on stock return. Original Article | Turnitin